The influence of operating capacity, leverage, and cash flow on financial distress with firm size as moderating Variable - Susanti, Erni; Arismaya, Anisa Dewi; Nubatonis, George Ardianto Simson (Islamic Accounting Journal, 2024)
This research aims to examine the influence of operating capacity, leverage and cash flow on financial distress with firm size as a moderating variable in energy sector companies registered with ISSI for the 2020-2023 period. This research uses quantitative methods with Moderated Regression Analysis (MRA) as a data analysis tool. By using purposive sampling, a sample of 24 energy sector companies registered with ISSI was obtained. This research uses secondary data in the form of panel data from company financial reports published on the Indonesian Stock Exchange. The analysis used in this research is multiple linear regression analysis with Eviews Version 12 software. The T test results show that Operating Capacity and cash flow have a positive and significant effect on financial distress. Meanwhile, leverage has no effect on financial distress. The results of the moderation test in this study show that firm size is unable to moderate the influence of operating capacity on financial distress, while firm size is able to moderate the influence of leverage and cash flow on financial distress. Keywords: Operating Capacity, Leverage, Cash Flow, Financial Distress, Firm Size.